The Effectiveness of Education Using Virtual Reality Video Media on Oral Health Knowledge in Elementary School Students 10 Sungai Sapih, Padang City - DM, Hafizah Oulya; Arma, Utmi; Ningrum, Valendriyani (Indonesian Dental Association, 2023)
Introduction: Virtual reality (VR) is a technology that creates a simulated version of the real world. In recent years, VR has been increasingly utilized as a tool in education due to its potential to enhance the learning experience. One of the factors that causes oral health problems is the low level of knowledge of individual children. Objectives: this study aims to determine the effectiveness of education using virtual reality video media on dental and oral health knowledge in students of SDN 10 Sungai Sapih, Padang. Method: This is quasi-experimental research with a one-group pre-test post-test design. Convenience sampling was used to select 40 participants who met the inclusion criteria. Statistical analysis to determine the effectiveness of the use of VR media in increasing dental health knowledge using the Wilcoxon non-parametric test. Results: The study found that the average student knowledge score increased from 11.30 to 13.20 after using VR media for education. The Wilcoxon test results indicate a significant difference before and after the VR media intervention, with a p value of 0.000 (<0.05). Conclusion: The study concludes that the use of virtual reality video media in education is effective in improving oral health knowledge among students of SDN 10 Sungai Sapih, Padang City. VR media is very innovative to be implemented in the classroom, however it requires readiness from teachers and schools to support the success of the media.